Separate regulation of transport and biosynthesis of leucine, isoleucine, and valine in bacteria. - Quay, S C (1975)
Since both transport activity and the leucine biosynthetic enzymes are repressed by growth on leucine, the regulation of leucine, isoleucine, and valine biosynthetic enzymes was examined in Escherichia coli K-12 strain EO312, a constitutively derepressed branched-chain amino acid transport mutant, to determine if the transport derepression affected the biosynthetic enzymes. Neither the iluB gene product, acetohydroxy acid synthetase (acetolactate synthetase, EC 4.1.3.18), NOR THE LEUB gene product, 3-isopropylmalate dehydrogenase (2-hydroxy-4-methyl-3-carboxyvalerate-nicotinamide adenine dinucleotide oxido-reductase, EC 1.1.1.85), were significantly affected in their level of derepression or repression compared to the parental strain. A number of strains with alterations in the regulation of the branched-chain amino acid biosynthetic enzymes were examined for the regulation of the shock-sensitive transport system for these amino acids (LIV-I). When transport activity was examined in strains with mutations leading to derepression of the iluB, iluADE, and leuABCD gene clusters, the regulation of the LIV-I transport system was found to be normal. The regulation of transport in an E. coli strain B/r with a deletion of the entire leucine biosynthetic operon was normal, indicating none of the gene products of this operon are required for regulation of transport. Salmonella typhimurium LT2 strain leu-500, a single-site mutation affecting both promotor-like and operator-like function of the leuABCD gene cluster, also had normal regulation of the LIV-I transport system. All of the strains contained leucine-specific transport activity, which was also repressed by growth in media containing leucine, isoleucine and valine. The concentrated shock fluids from these strains grown in minimal medium or with excess leucine, isoleucine, and valine were examined for proteins with leucine-binding activity, and the levels of these proteins were found to be regulated normally. It appears that the branched-chain amino acid transport systems and biosynthetic enzymes in E. coli strains K-12 and B/r and in S. typhimurium strain LT2 are not regulated together by a cis-dominate type of mechanism, although both systems may have components in common.